Quantification of oxygen metabolic rates in Human brain with dynamic 17O MRI: Profile likelihood analysis. Issue 3 (1st November 2016) - Kurzhunov, Dmitry; Borowiak, Robert; Hass, Helge; Wagner, Philipp; Krafft, Axel Joachim; Timmer, Jens; Bock, Michael
Abstract : Purpose: Parameter identifiability and confidence intervals were determined using a profile likelihood (PL) analysis method in a quantification model of the cerebral metabolic rate of oxygen consumption (CMRO2 ) with direct 17 O MRI. Methods: Three‐dimensional dynamic 17 O MRI datasets of the human brain were acquired after inhalation of 17 O2 gas with the help of a rebreathing system, and CMRO2 was quantified with a pharmacokinetic model. To analyze the influence of the different model parameters on the identifiability of CMRO2, PLs were calculated for different settings of the model parameters. In particular, the 17 O enrichment fraction of the inhaled 17 O2 gas, α, was investigated assuming a constant and a linearly varying model. Identifiability was analyzed for white and gray matter, and the dependency on different priors was studied. Results: Prior knowledge about only one α ‐related parameter was sufficient to resolve the CMRO2 nonidentifiability, and CMRO2 rates (0.72–0.99 µmol/gtissue /min in white matter, 1.02–1.78 µmol/gtissue /min in gray matter) are in a good agreement with the results of 15 O positron emission tomography studies. Nonconstant α values significantly improved model fitting. Conclusion: The profile likelihood analysis shows that CMRO2 can be measured reliably in 17 O gas MRI experiment if the 17 O enrichment fraction is used as prior information for the model calculations. Magn Reson Med 78:1157–1167, 2017. © 2016 International Society for Magnetic Resonance in Medicine.